Peran Media Pembelajaran Terhadap Rasio Guru-Murid di TPA Al-Falah: Peran Media Pembelajaran Terhadap Rasio Guru-Murid di TPA Al-Falah - Purwantoro, Hanan; Galih Aisia, Galih Aisia; Rizkya Fatikha, Rizkya Fatikha; Aniisah Naadiah, Aniisah Naadiah; Arini Rifk; Riza (BIDIK: Jurnal Pengabdian kepada Masyarakat, 2025)
The limited number of teachers at Al-Falah Qur'anic Education Centre (TPA), only three, is a crucial problem that has a significant impact on the quality of teaching and the development of children. The unbalanced ratio of teachers and students is the root of the problem. This programme offers a solution in the form of developing memorisation cards and snakes and ladders educational games to improve learning effectiveness. Hopefully, this programme can have a positive impact on teachers and children in the process of religious learning.